Mouse genetics and proteomic analyses demonstrate a critical role for complement in a model of DHRD/ML, an inherited macular degeneration - Garland, Donita L. (Oxford University Press, 2014)
Macular degenerations, inherited and age related, are important causes of vision loss. Human genetic studies have suggested perturbation of the complement system is important in the pathogenesis of age-related macular degeneration. The mechanisms underlying the involvement of the complement system are not understood, although complement and inflammation have been implicated in drusen formation. Drusen are an early clinical hallmark of inherited and age-related forms of macular degeneration. We studied one of the earliest stages of macular degeneration which precedes and leads to the formation of drusen, i.e. the formation of basal deposits. The studies were done using a mouse model of the inherited macular dystrophy Doyne Honeycomb Retinal Dystrophy/Malattia Leventinese (DHRD/ML) which is caused by a p.Arg345Trp mutation in EFEMP1. The hallmark of DHRD/ML is the formation of drusen at an early age, and gene targeted Efemp1(R345W/R345W) mice develop extensive basal deposits. Proteomic analyses of Bruch's membrane/choroid and Bruch's membrane in the Efemp1(R345W/R345W) mice indicate that the basal deposits comprise normal extracellular matrix (ECM) components present in abnormal amounts. The proteomic analyses also identified significant changes in proteins with immune-related function, including complement components, in the diseased tissue samples. Genetic ablation of the complement response via generation of Efemp1(R345W/R345W):C3(−/−) double-mutant mice inhibited the formation of basal deposits. The results demonstrate a critical role for the complement system in basal deposit formation, and suggest that complement-mediated recognition of abnormal ECM may participate in basal deposit formation in DHRD/ML and perhaps other macular degenerations.